FUNGSI TOKOH SUPERNATURAL DAN WACANA TENTANG PEREMPUAN CERPEN “PINTU MERAH” DAN “JERITAN DALAM BOTOL” KARYA INTAN PARAMADITHA (Supernatural Characters and Discourse about Woman in Short Stories “Pintu Merah” and “Jeritan dalam Botol” Written by Intan Paramadita) - Kurnianto, Ery Agus (Balai Bahasa Sumatra Barat, 2014)
This paper focuses on strategic issues in the text display function supernatural figure inbreaking down the discourse about women in short stories “Pintu Merah” dan “Jeritan dalamBotol” written by Intan Paramaditha. The purpose of this article is to show how the strategyfunction displays text in a supernatural figure in breaking down the discourse on women whoalready grounded by the patriarchy. The method used in this research is descriptive method.The theory used is the theory of gender categories. The conclusion is that supernatural figuresshown by the diamonds in the short story “Pintu Merah” dan “Jeritan dalam Botol” has thefunction to urge all civility and patriarchal norms to be dismantled. Women’s issues rosethrough the dark silence as a form of business worrisome to escape the pressure. Femaleresistance to patriarchal norms that appear in the short story Pintu Merah dan Jeritan dalamBotol tends to be closed, silent, silent and tend to be inward.Keywords: supenatural character, discourse about women.